Bridging Theory and Practice: A Scoping Review Examining Postsecondary Vocational Flipped Classrooms - Byers Reid, Tracy; Jin, WanQi (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2026)
This scoping review explores flipped classroom (FC) instructional design strategies in postsecondary vocational education, specifically focusing on how they influence student engagement. As institutions increasingly adopt blended learning to address the evolving needs of adult learners, the FC model offers one approach by shifting foundational content delivery to pre‑class online activities and reserving in‑person sessions for interactive tasks that foster deeper engagement and active learning. Guided by Arksey and O'Malley’s (2005) scoping review framework, this review analyzed 18 peer‑reviewed sources published between April 2018 and February 2025. Findings reveal that effective FCs intentionally align online and in‑person components, using pre‑class materials to build foundational knowledge and in‑class activities to support higher‑order thinking. Engagement is most often conceptualized behaviourally and fostered through purposefully designed pre‑class content, in‑class collaboration, and ongoing instructor support. The review also identifies challenges such as students’ inconsistent pre‑class preparation and instructors’ need for pedagogical and technical skills. Gaps in the literature highlight limited research on assessment design and longitudinal FC implementation. This review highlights the need for ongoing research into targeted engagement strategies and offers practical guidance for educators and instructional designers aiming to bridge the gap between theory and practice in vocational FC contexts.